"I'm a Different Coach With Every Family": Early Interventionists' Beliefs and Practices. Issue 3 (July 2018) - Meadan, Hedda; Douglas, Sarah N.; Kammes, Rebecca; Schraml-Block, Kristen
Abstract : Early intervention (EI) service providers working with young children with developmental disabilities and delays and their families often utilize coaching practices to engage caregivers in the EI process. Within the literature, the usefulness of coaching has been identified. However, little is known about how coaching practices look in naturalistic settings and service providers' perceptions of these practices. Through the use of an online survey, this study examined beliefs and reported practices of EI service providers. The findings indicated that EI providers considered coaching to be meaningful and offered several benefits to both caregivers and children. Some of the perceived advantages included engaging and empowering caregivers and increased opportunities for children to practice and master skills. Most coaching practices were ranked as highly important and were reportedly utilized frequently by service providers in the sample. However, some coaching practices, such as reflection and feedback, were not implemented as often as joint planning, observation, and action. In addition, the participants identified challenges and facilitators for using coaching as a style of interacting with caregivers. Discussion of EI provider perceptions, limitations, recommendations, implications, and future research directions are presented.